2022
DOI: 10.3390/cells11111723
|View full text |Cite
|
Sign up to set email alerts
|

Different Methods for Evaluating Microglial Activation Using Anti-Ionized Calcium-Binding Adaptor Protein-1 Immunohistochemistry in the Cuprizone Model

Abstract: Microglia play an important role in the pathology of various central nervous system disorders, including multiple sclerosis (MS). While different methods exist to evaluate the extent of microglia activation, comparative studies investigating the sensitivity of these methods are missing for most models. In this study, we systematically evaluated which of the three commonly used histological methods (id est, quantification of microglia density, densitometrically evaluated staining intensity, or cellular morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…The lack of NeuN in the hippocampus may indicate transcriptional changes and not a complete loss of neuronal function between groups, as NeuN is a marker for neuronal nuclear protein [28]. Additionally, our analysis of Iba-1 is based on cytoplasmic density as an indicator of pathologically activated amoeboid microglia [23, 24], which, although we believe is the most reliable measurement to assess actin-bundling activity and thus the membrane ruffling and phagocytotic state in activated microglia [29], other ways to interpret our analysis may produce a different conclusion on pathological activation. Lastly, as it is known that Iba-1 marks both microglia and infiltrating macrophages [30], additional studies may be necessary to determine the exact immune response caused by MA10 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of NeuN in the hippocampus may indicate transcriptional changes and not a complete loss of neuronal function between groups, as NeuN is a marker for neuronal nuclear protein [28]. Additionally, our analysis of Iba-1 is based on cytoplasmic density as an indicator of pathologically activated amoeboid microglia [23, 24], which, although we believe is the most reliable measurement to assess actin-bundling activity and thus the membrane ruffling and phagocytotic state in activated microglia [29], other ways to interpret our analysis may produce a different conclusion on pathological activation. Lastly, as it is known that Iba-1 marks both microglia and infiltrating macrophages [30], additional studies may be necessary to determine the exact immune response caused by MA10 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Counting of NeuN in each region of the hippocampus was defined by complete circumferential signal intensity of each cell. Scoring of Iba-1 positive microglia in the hippocampus was done via cytoplasm analysis and defined as G1 (0-30%), G2 (30-60%), and G3 (60-100%) as relative percentages of signal intensity based on previously characterized ameboid-like Iba-1 positive microglia phenotypes which exhibits a hypertrophic cell body correlating to an activated state [23, 24]. All scoring was done blinded.…”
Section: Methodsmentioning
confidence: 99%
“…Imaging was performed with Andor Dragonfly spinning disk confocal microscope. Marker fluorescence and microglia counts, intensity, and ramification indices (method based on previous work 51 ) were quantified with Fiji (confocal microscope set up in Extended Methods Table 4 and macros downloadable from the public Github repository). Ramification indices of 0-1 of objects with a threshold size of 19 mm 2 were quantified from three Z-stack images/mouse and two mice/group.…”
Section: Mouse Histology and Confocal Microscopymentioning
confidence: 99%
“…Microglial activation can be determined by various parameters such as cell number, morphology, gene expression, or cytokines. In the hippocampus, it was demonstrated that the extent of microglial cell activation increased with an increase in the “number of microglial cells” [ 15 ]. To further investigate microglia-mediated neuroinflammation after chronic UV exposure, we conducted immunohistochemical evaluation of microglial activation.…”
Section: Main Textmentioning
confidence: 99%
“…The discrepancy between immunostaining and mRNA assays has also been reported in previous studies. Furthermore, immunostaining that can detect changes in the number and morphology of micrmicroglia has been suggested as a sensitive marker for activated microglia [ 15 ]. Also, the correlation between downregulation of specific microglia-related genes and microglial activation requires further investigation.…”
Section: Main Textmentioning
confidence: 99%